Population limitation and the wolves of Isle Royale - Peterson, Rolf O.; Thomas, Nancy J.; Thurber, Joanne M.; Vucetich, John A.; Waite, Thomas A. (Journal of Mammalogy, 1998)
Population regulation for gray wolves in Isle Royale National Park, Michigan, was examined in 1987-1995 when wolves were in chronic decline following a crash of the population in 1981-1982. Canine parvovirus (CPV-2) was probably influential during the crash, but it disappeared by the late 1980s. High mortality abruptly ceased after 1988, but low recruitment in the absence of disease and obvious shortage of food prevented recovery of the wolf population. In 1983-1995, with a comparable number of moose ≥ 10 years old as potential prey, wolves were only half as numerous as in 1959-1980. A simulation of annual fluctuations in effective population size (Ne) for wolves on Isle Royale suggests that their genetic heterozygosity has declined ca. 13% with each generation and ca. 80% in the 50-year history of this population. Inbreeding depression and stochastic demographic variation both remain possible explanations for recent low recruitment.